2019
DOI: 10.1007/jhep05(2019)202
|View full text |Cite
|
Sign up to set email alerts
|

Wilson loops in terms of color invariants

Abstract: We derive an expression for the vacuum expectation value (vev) of the 1/2 BPS circular Wilson loop of N = 4 super Yang Mills in terms of color invariants, valid for any representation R of any gauge group G. This expression allows us to discuss various exact relations among vevs in different representations. We also display the reduction of these color invariants to simpler ones, up to seventh order in perturbation theory, and verify that the resulting expression is considerably simpler for the logarithm of W … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 91 publications
(152 reference statements)
0
40
0
Order By: Relevance
“…A straightforward application of our results allows to generalize the recent observation [40,48] that the generating functions for Wilson loops in the totally symmetric and totally antisymmetric representations are related to each other by changing the signs of the generating parameter (y in our case) and of N . It was remarked in [41] that this is a general property for Wilson loops in conjugate representations. In our formulation, this property would read 7 W y;…”
Section: Discussionmentioning
confidence: 82%
“…A straightforward application of our results allows to generalize the recent observation [40,48] that the generating functions for Wilson loops in the totally symmetric and totally antisymmetric representations are related to each other by changing the signs of the generating parameter (y in our case) and of N . It was remarked in [41] that this is a general property for Wilson loops in conjugate representations. In our formulation, this property would read 7 W y;…”
Section: Discussionmentioning
confidence: 82%
“…He conjectured that this relation is exact in λ. In [31], it was shown that this is actually an example of a general relation between the Wilson loops in representations corresponding to transpose Young diagrams, in this case,…”
Section: Introductionmentioning
confidence: 89%
“…The proof in [31] was based on an expansion in terms of color invariants and is formally perturbative in powers of g 2 Y M , or, equivalently, λ. An expansion in 1/N requires further work.…”
Section: Introductionmentioning
confidence: 99%
“…where B is called the Bremsstrahlung function 7 . For Lagrangian CFTs with N = 2 supersymmetry this function can be computed using supersymmetric localization 6,8,9 . For N = 2 SCFTs it was argued 8,10 and then proved 11 that B = 3h.…”
Section: Introductionmentioning
confidence: 99%